(untitled) (GYMNASIUM, 2017)
The aim and tasks of this paper represent the desire to contribute to the improvement of physical education teaching at seventh grade, by using handball dynamic games. The study was conducted at the "Stefan cel Mare" National College, in Bacău, over the course of approximately one year, 2012-2013, the experimental group comprising 11 boys and 14 girls, and the control group, 14 girls and 11 boys. The results presented for each drill, in the two stages, initial and final, are accompanied by the results imposed by the standards of the curriculum. We can say that the use of dynamic games and specific handball relays ensured a growing efficiency of the physical education lessons, thus confirming our initial hypothesis. The dynamic games enhanced the motivation of all students, boys and girls alike, determining them to engage themselves in the specific effort, assimilating the knowledge and skill necessary for playing handball.